Z-type heterojunction photocatalyst as well as preparation method and application thereof
By developing Z-type heterojunction photocatalysts, combined with the combination of graphite phase carbon nitride, silver and barium titanate, key issues in hydrogen energy production and environmental pollution control have been solved, and efficient nitrogen fixation and tetracycline degradation effects have been achieved.
Patent Information
- Application Number
- CN202411597640.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-11
- Publication Date
- 2025-02-14
AI Technical Summary
The existing technology is difficult to efficiently solve the key problems in hydrogen energy production and environmental pollution control, especially the high-energy consumption production of ammonia and the pollution of tetracycline antibiotics in water bodies.
Develop a Z-type heterojunction photocatalyst, specifically a graphite phase carbon nitride/silver/barium titanate photocatalyst, through a specific preparation method, including spherical g-C3N4, barium titanate BaTiO3 and silver nanoparticles, to form Composite materials to improve photocatalytic properties.
Under the combined action of the piezoelectric effect of barium titanate and the SPR effect of silver nanoparticles, this photocatalyst significantly improves the efficiency of nitrogen fixation and tetracycline degradation, solving the challenges in hydrogen energy production and environmental pollution control.
Smart Images

Figure CN119425758A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of photocatalysts, and in particular relates to a Z-type heterojunction photocatalyst and a preparation method and application thereof. Background Art
[0002] Hydrogen has received widespread attention as a future fuel and an important means to achieve this goal. However, the production, storage and transportation of hydrogen still face challenges. Clean energy ammonia (NH3) as a stable hydrogen carrier and efficient conversion of ammonia to hydrogen through catalytic technology are effective ways to address these challenges. At present, the production of ammonia mainly relies on the Haber-Bosch process with high energy consumption and high CO2 emissions. At the same time, the residual problem of tetracycline antibiotics in water bodies is becoming increasingly serious, and photocatalytic technology has become an effective method for dealing with such pollution due to its mild, environmentally friendly and low energy consumption. Therefore, the development of efficient semiconductor photocatalysts is crucial for nitrogen fixation and pollutant degradation. Summary of the invention
[0003] The technical problem to be solved by the present invention is to provide a Z-type heterojunction photocatalyst and a preparation method and application thereof, which effectively solves the key problems in current hydrogen energy production and environmental pollution control.
[0004] The invention provides a Z-type heterojunction photocatalyst, wherein the photocatalyst is a graphite phase carbon nitride / silver / barium titanate photocatalyst.
[0005] The present invention also provides a method for preparing a Z-type heterojunction photocatalyst, comprising the following steps: (1) Melamine and cyanuric acid are mixed in a solvent, stirred, centrifuged, dried, and calcined to obtain spherical g-C3N4, denoted as SCN; (2) dissolving titanate in an organic amine solution, adding an alkali solution and a barium-containing solution and stirring, then performing a hydrothermal reaction, washing, and drying to obtain barium titanate BaTiO3; (3) Adding silver salt and barium titanate to an organic solvent, and using a photodeposition method to deposit silver nanoparticles to obtain Ag / BaTiO3; (4) SCN and Ag / BaTiO3 are dissolved in an organic solvent at a mass ratio of 1:1-1:4, subjected to ultrasonic treatment, washed and dried to obtain the Z-type heterojunction photocatalyst, hereinafter referred to as SCN@AB composite material.
[0006] Preferably, the mass ratio of melamine to cyanuric acid is 1:1.
[0007] Preferably, the solvent in step (1) includes one or more of dimethyl sulfoxide, N,N-dimethylacetamide, N,N-dimethylformamide, N-methylpyrrolidone, hexamethylphosphoric acid triamide, and glycerol.
[0008] Preferably, the mixing temperature in step (1) is 5-180°C.
[0009] Preferably, the stirring speed in step (1) is controlled between 50 and 600 rpm, and the stirring time lasts for 0.2 to 4 hours.
[0010] Preferably, the centrifugal speed in step (1) is 500-8000 rpm.
[0011] Preferably, the drying temperature in step (1) is 80-90°C.
[0012] Preferably, the calcination in step (1) is specifically carried out in an argon, oxygen or nitrogen atmosphere at a temperature range of 200-900° C. for a duration of 1-24 hours.
[0013] Preferably, the titanate in step (2) includes one or more of tetra-n-butyl titanate, tetra-isopropyl titanate, tetra-ethyl titanate, tetra-butoxytitanium titanate, and titanium tert-butoxide.
[0014] Preferably, the organic amine in step (2) includes one or more of ethanolamine, diethanolamine, triethanolamine and isopropanolamine.
[0015] Preferably, the alkaline solution in step (2) comprises one or more of potassium hydroxide, calcium hydroxide and sodium hydroxide.
[0016] Preferably, the barium-containing solution in step (2) comprises one or more of barium sulfate, barium carbonate, barium nitrate, barium chloride and barium hydroxide solution.
[0017] Preferably, the volume ratio of the titanate, the organic amine, the alkaline solution, and the barium-containing solution is 30-200: 10-50: 0.5-1000: 0.1-2. The concentration of the alkaline solution is 0.1 mol / L-10 mol / L. The concentration of the barium-containing solution is 1 mol / L-2 mol / L.
[0018] Preferably, the stirring speed in step (2) is set to 100-800 rpm, the temperature is maintained at 25-75° C., and the time is about 1-6 hours.
[0019] Preferably, the hydrothermal reaction in step (2) is specifically: treating at a temperature of 100-280° C. for 1-48 hours.
[0020] Preferably, the organic solvent in step (3) includes one or more of ethanol, acetone, ethyl acetate, toluene and xylene.
[0021] Preferably, the silver salt in step (3) includes one or more of silver nitrate, silver chloride, silver bromide and silver iodide.
[0022] Preferably, the concentration of the silver salt in the organic solvent is 0.01 mol / L to 2 mol / L. The mass ratio of the silver salt to barium titanate is 2:1.
[0023] Preferably, the deposition in step (3) is specifically as follows: the light intensity is 50-5000 mW / cm, and the deposition time lasts 0.1-50 hours.
[0024] Preferably, the organic solvent in step (4) includes one or more of methanol, isopropanol, butanol, ethylene glycol, n-propanol, 1-pentanol, isopentanol, and ethanolamine.
[0025] Preferably, the ultrasonic treatment in step (4) is as follows: each treatment time is 10 to 60 minutes, and the total ultrasonic time does not exceed 2 hours.
[0026] Preferably, deionized water is used in the washing process in step (4), and the number of washing times is 3 to 7 times.
[0027] Preferably, the drying temperature in step (4) is 40-80°C.
[0028] The present invention also provides an application of a Z-type heterojunction photocatalyst in nitrogen fixation or pollutant degradation.
[0029] Figure 1 The energy band position relationship of SCN, BaTiO3 and SCN@AB composites in the photocatalytic process, as well as the transfer path of electrons and holes, are demonstrated. Under visible light irradiation, electron-hole transfer will occur between the composites, promoting the redox reaction. Ultrasonic vibration will cause internal polarization of BaTiO3, generate a polarized internal electric field, and promote the separation and transfer of electrons and holes inside BaTiO3. Under the local plasma resonance effect of the electronic medium Ag nanoparticles, the holes on the SCN valence band and the electrons on the BaTiO3 conduction band undergo charge transfer and recombination, forming an all-solid-state Z-type heterojunction. This can effectively reduce the recombination of electrons and holes inside the material and promote efficient redox reactions between electrons on the SCN conduction band and holes on the BaTiO3 valence band.
[0030] Beneficial Effects The Z-type heterojunction photocatalyst of the present invention exhibits excellent light absorption capacity and charge separation transfer efficiency under the combined action of the piezoelectric effect of barium titanate and the SPR effect of silver nanoparticles, significantly improving the efficiency of nitrogen fixation and tetracycline degradation. The catalyst not only helps to solve the challenges in hydrogen energy production, but also provides an effective means for the removal of tetracycline antibiotics in water bodies, which is of great significance to the utilization of renewable energy and environmental protection. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] Figure 1 Schematic diagram of the mechanism of the 1:3-SCN@AB composite material Z-type heterojunction photocatalyst prepared in Example 3 of the present invention.
[0032] Figure 2 XRD patterns (a), FTIR spectra (b), nitrogen adsorption-desorption patterns of different samples prepared in Example 3 of the present invention, with the inset being the pore size distribution pattern (c) and XPS spectra (d).
[0033] Figure 3 SEM images (ad) of different samples prepared in Example 3 of the present invention; TEM images (eg) of different samples; HETEM image (h), selected area electron diffraction (SAED) image (i) and elemental mapping image (j) of the 1:3-SCN@AB composite material.
[0034] Figure 4 Photocatalytic nitrogen fixation performance of different samples prepared in Example 3 of the present invention under a 300W Xe lamp with 10% methanol water as a sacrificial agent (a, b); control experiments under different conditions for the 1:3-SCN@AB composite material (c) and cyclic stability experiments of the 1:3-SCN@AB composite material (d).
[0035] Figure 5 Comparison of the degradation efficiency of TC under simulated visible light irradiation of different samples prepared in Example 3 of the present invention (a); Changes in the apparent rate constants of different samples (b); Derivation of the apparent rate constant k of photocatalytic degradation of different samples (c); Free radical capture experiment of 1:3-SCN@AB composite material (d).
[0036] Figure 6 UV-visible diffuse reflectance spectra of different samples prepared in Example 3 of the present invention (a); band gap energy of SCN and BaTiO3 (b); Mott-Schottky plots of SCN and BaTiO3 (c, d). DETAILED DESCRIPTION
[0037] The present invention will be further described below in conjunction with specific embodiments. It should be understood that these embodiments are only used to illustrate the present invention and are not intended to limit the scope of the present invention. In addition, it should be understood that after reading the content taught by the present invention, those skilled in the art can make various changes or modifications to the present invention, and these equivalent forms fall within the scope limited by the appended claims of the application equally.
[0038] Example 1 (1) 0.5 g of melamine and 0.5 g of cyanuric acid were mixed in 25 and 17 mL of dimethyl sulfoxide at room temperature, respectively, with the stirring speed controlled at 100 rpm for 2 hours. After that, the product was separated by centrifugation at a speed of 1000 rpm, washed several times to remove impurities, and dried at 80 ° C. Finally, it was calcined at 550 ° C for 4 hours under nitrogen atmosphere to obtain light yellow powder spherical g-C3N4, recorded as SCN.
[0039] (2) 1.7 ml of tetrabutyl titanate was slowly dripped into 20 ml of ethanolamine, and 25 ml of 14.4 mol / L sodium hydroxide solution and 5 ml of 1 mol / L barium chloride solution were added at the same time. The reaction temperature was maintained at 25 ° C, the stirring speed was set to 600 rpm, and the reaction time was about 1 hour. Subsequently, it was treated at 200 ° C for 24 hours by hydrothermal reaction, and then washed and dried to obtain white powder barium titanate BaTiO3.
[0040] (3) Add 0.4 g of silver nitrate and 0.2 g of barium titanate to 50 mL of ethanol solution, and deposit silver nanoparticles by photodeposition under infrared light conditions. The light intensity is 1000 mW / cm and the deposition time is 24 hours to obtain Ag / BaTiO3, which is recorded as AB. (4) SCN and Ag / BaTiO3 were dissolved in 50 mL of isopropanol in a mass ratio of 1:1 and subjected to ultrasonic treatment for 20 minutes each time. After mixing, ultrasonic treatment was continued for a total of no more than 2 hours. Deionized water was used in the washing process for 3 times, and finally dried at 80°C to obtain the Z-type heterojunction photocatalyst, which was recorded as 1:1-SCN@AB composite material.
[0041] Example 2 The difference from Example 1 is that the mass ratio of SCN to Ag / BaTiO3 is 1:2, which is recorded as 1:2-SCN@AB composite material.
[0042] Example 3 The difference from Example 1 is that the mass ratio of SCN to Ag / BaTiO3 is 1:3, which is recorded as 1:3-SCN@AB composite material.
[0043] Example 4 The difference from Example 1 is that the mass ratio of SCN to Ag / BaTiO3 is 1:4, which is recorded as 1:4-SCN@AB composite material.
[0044] Test results: (1) XRD analysis Figure 2 a) Confirmation of the successful preparation of SCN@AB composites. The strong peak of SCN at 27.6° corresponds to the (002) diffraction plane of the layered conjugated aromatic structure, while the weaker diffraction peak at 12.8° corresponds to the (100) diffraction plane of the heptazine unit in the repeating plane. The diffraction peaks of BaTiO3 correspond to the (100), (110), (111), (002), (200), (210), (211), (220), (300), (310) and (311) crystal planes. The XRD peaks of AB are not visible due to the low content of Ag nanoparticles. As the AB content increases, the peak intensity of SCN gradually weakens, but the peak position does not change.
[0045] FTIR spectroscopy ( Figure 2 b) The chemical structures of the samples were analyzed. The absorption band of SCN at 811 cm^-1 is attributed to the bending vibration of the triazine ring, and the absorption peaks in the region of 1200-1700 cm^-1 are attributed to the stretching vibrations of CN and C=N heterocycles. The peaks of BaTiO3 at 425 and 556 cm^-1 are attributed to the bending vibration and stretching vibration of Ti-O, respectively. The bending vibration of adsorbed water was observed at 1632 cm^-1. The broad absorption peaks in the range of 3000-3600 cm^-1 are attributed to the stretching vibrations of OH of water and NH of free amino groups on the surface of SCN. The slight addition of Ag nanoparticles has little effect on the significant FTIR peaks of SCN@AB nanocomposites, but it affects the absorption parameters.
[0046] All samples ( Figure 2 c) Both of them show type IV isotherms with H3 hysteresis loops, indicating that they all have mesoporous structures. After coupling with AB, the specific surface area of 1:3-SCN@AB (29.06 cm -1 ) is smaller than SCN (50.01cm -1 ), which may be due to the fact that BaTiO3 (specific surface area of 4.01 cm -1 ) covers part of the surface voids of the SCN.
[0047] XPS spectra ( Figure 2 d) The chemical states of the synthesized composites were analyzed. The complete XPS spectra of SCN and 1:3-SCN@AB composites contain significant signal peaks of C1s, N 1s, O 1s, Ag 3d, Ba 3d, and Ti2p, as well as the contents of each element.
[0048] (2) Figure 3 a shows the morphology of the g-C3N4 precursor, which is a nanoflower ball structure of uniform size, composed of many thin sheets. This structure can effectively increase the specific surface area of the material, thereby enhancing the photocatalytic performance. Figure 3 b shows the tetragonal phase of BaTiO3, which is about 200 nm in size. Figure 3 c Ag nanoparticles were observed to be uniformly dispersed on the surface of BaTiO3. Figure 3 d shows the morphology of the 1:3-SCN@AB composite, indicating that AB is more evenly dispersed on the SCN nanoflower balls. Figure 3 e is the HR-TEM image of the 1:3-SCN@AB composite material, showing clear lattice fringes with a lattice spacing of 0.282 nm, corresponding to the crystal plane of BaTiO3(110). Figure 3 f, g are TEM images of 1:3-SCN@AB. Figure 3 h is its HRTEM image. Figure 3 i is the selected area electron diffraction (SAED) pattern of the 1:3-SCN@AB composite material, showing a single diffraction ring of the composite material. Figure 3 j is the element mapping of 1:3-SCN@AB composite material, which reveals the presence of six elements, C, N, Ag, Ba, Ti and O, and these elements are evenly distributed in the sample.
[0049] (3) Figure 4 a and b show the photocatalytic nitrogen fixation performance of different samples under 300W Xe lamp with 10% methanol water as sacrificial agent. The NH3 yields of SCN, BaTiO3, AB, 1:1-SCN@AB, 1:2-SCN@AB, 1:3-SCN@AB, and 1:4-SCN@AB are 357.38, 197.4, 411.84, 462.9, 554.81, 765.85, and 707.949 μmol·g, respectively. -1 ·h -1 1:3-SCN@AB has the highest nitrogen fixation efficiency of 765.85 μmol·g -1 ·h -1 .
[0050] Figure 4 c is a control experiment of 1:3-SCN@AB composite material under different conditions, including stirring, Ar gas, no light and no catalyst. The nitrogen fixation performance decreased under stirring conditions, which may be due to the weakening of the piezoelectric properties of BaTiO3. Almost no NH3 was produced under Ar gas conditions, indicating that N2 is the main source of elemental N in NH3. No NH3 was produced under no light and no catalyst, proving that light and catalyst play a key role in the nitrogen fixation process. Figure 4 d is the cyclic stability experiment of 1:3-SCN@AB composite material. The nitrogen fixation efficiency decreased slightly during the cyclic experiment, but the XRD and SEM images showed that the structure of the composite material was stable without obvious changes.
[0051] (4) Figure 5 a is the comparison of TC degradation efficiency of different samples under simulated visible light irradiation. 1:3-SCN@AB has the highest TC degradation efficiency of 82.7%. Figure 5 b is the change diagram of the apparent rate constants of different samples, indicating that the photocatalytic degradation process conforms to the first-order kinetic model. Figure 5 c is the derivation diagram of the apparent rate constant k of photocatalytic degradation. The apparent rate constant of 1:3-SCN@AB composite material is 0.637h -1 . Figure 5 d is the free radical capture experiment. The removal rates of TC by TEOA, K2S2O4, IPA and BQ are 47.4%, 59.7%, 46.5% and 67.3%, respectively. + and OH are the main active substances, e - and O 2- Play a secondary role.
[0052] (5) Figure 6 a The light absorption efficiency of different samples was evaluated. The visible light absorption edge of SCN is at 450nm, and that of BaTiO3 is at 400nm; Ag / BaTiO3 has significantly enhanced light absorption in the visible range due to the SPR effect of Ag nanoparticles; the 1:3-SCN@AB composite material has the largest light absorption range. Figure 6 b Band gaps of SCN and BaTiO3 calculated according to the Tauc equation. The band gaps of SCN and BaTiO3 are 2.72 and 2.98 eV, respectively. Figure 6 c and d are used to analyze the flat band potential and semiconductor type. The flat band potentials of SCN and BaTiO3 are -0.74 and -0.26 eV (vs NHE) respectively, and both are n-type semiconductors; for n-type semiconductors, the flat band potential is 0.1-0.3V more positive than the conduction band potential, so the conduction band potentials of SCN and BaTiO3 are -0.94 and -0.46 eV (vs NHE) respectively; from the band gap width, it can be seen that the valence band potentials are 1.78 and 2.52 eV respectively. The energy band position relationship of each material can be clearly known.
Claims
1. A Z-type heterojunction photocatalyst, characterized in that: The photocatalyst is a graphite phase carbon nitride / silver / barium titanate photocatalyst.
2. A method for preparing a Z-type heterojunction photocatalyst, characterized in that: The steps include: (1) Melamine and cyanuric acid are mixed in a solvent, stirred, centrifuged, dried, and calcined to obtain spherical g-C3N4, denoted as SCN; (2) dissolving titanate in an organic amine solution, adding an alkali solution and a barium-containing solution and stirring, then performing a hydrothermal reaction, washing, and drying to obtain barium titanate BaTiO3; (3) Adding silver salt and barium titanate to an organic solvent, and using a photodeposition method to deposit silver nanoparticles to obtain Ag / BaTiO3; (4) SCN and Ag / BaTiO3 are dissolved in an organic solvent at a mass ratio of 1:1-1:4, subjected to ultrasonic treatment, washed and dried, and the Z-type heterojunction photocatalyst is obtained.
3. The preparation method according to claim 2, characterized in that: The mass ratio of melamine to cyanuric acid in step (1) is 1:
1.
4. The preparation method according to claim 2, characterized in that: The solvent in step (1) includes one or more of dimethyl sulfoxide, N,N-dimethylacetamide, N,N-dimethylformamide, N-methylpyrrolidone, hexamethylphosphoric acid triamide, and glycerol.
5. The preparation method according to claim 2, characterized in that: The titanate in step (2) includes one or more of tetra-n-butyl titanate, tetraisopropyl titanate, tetraethyl titanate, tetrabutoxytitanium titanate, and titanium tert-butoxide; the organic amine includes one or more of ethanolamine, diethanolamine, triethanolamine, and isopropanolamine.
6. The preparation method according to claim 2, characterized in that: The alkaline solution in step (2) includes one or more of potassium hydroxide, calcium hydroxide, and sodium hydroxide; the barium-containing solution includes one or more of barium sulfate, barium carbonate, barium nitrate, barium chloride, and barium hydroxide solution.
7. The preparation method according to claim 2, characterized in that: The organic solvent in step (3) includes one or more of ethanol, acetone, ethyl acetate, toluene, and xylene; the silver salt includes one or more of silver nitrate, silver chloride, silver bromide, and silver iodide.
8. The preparation method according to claim 2, characterized in that: The organic solvent in step (4) includes one or more of methanol, isopropanol, butanol, ethylene glycol, n-propanol, 1-pentanol, isopentanol, and ethanolamine.
9. The preparation method according to claim 2, characterized in that: The ultrasonic treatment in step (4) is specifically as follows: each treatment time is 10 to 60 minutes, and the total ultrasonic time does not exceed 2 hours.
10. Use of the Z-type heterojunction photocatalyst as claimed in claim 1 in nitrogen fixation or pollutant degradation.